2018
DOI: 10.1167/iovs.17-23304
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Considering the Middle Capillary Plexus on OCT Angiography in Diabetic Retinopathy

Abstract: PurposeTo quantify microvasculature changes in the superficial (SCP), middle (MCP), and deep capillary plexuses (DCP) in diabetic retinopathy (DR).MethodsRetrospective cross-sectional study at a tertiary academic referral center, in which 26 controls (44 eyes), 27 diabetic subjects without retinopathy (44 eyes), 32 subjects with nonproliferative retinopathy (52 eyes), and 27 subjects with proliferative retinopathy (40 eyes) were imaged with optical coherence tomography angiography (OCTA). Outcome measures incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
115
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(133 citation statements)
references
References 49 publications
15
115
3
Order By: Relevance
“…Moreover, recent studies also showed that additional segmentation and evaluation of the intermediate retinal layer from the superficial and deep retinal layers may enhance the ability of OCTA to detect early microvascular changes in diabetic eyes. 29,32,33 In this study, VAD and VSD were measured on the SRL, IRL, and DRL using our validated semiautomated segmentation algorithm. Our study showed that no significant difference was found in VSD or VAD in diabetic eyes without retinopathy compared to controls within the three vascular plexuses for a 6 × 6-mm scanning protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies also showed that additional segmentation and evaluation of the intermediate retinal layer from the superficial and deep retinal layers may enhance the ability of OCTA to detect early microvascular changes in diabetic eyes. 29,32,33 In this study, VAD and VSD were measured on the SRL, IRL, and DRL using our validated semiautomated segmentation algorithm. Our study showed that no significant difference was found in VSD or VAD in diabetic eyes without retinopathy compared to controls within the three vascular plexuses for a 6 × 6-mm scanning protocol.…”
Section: Discussionmentioning
confidence: 99%
“…), and the MCP seems to be of special interest (Onishi et al. ). The proprietary segmentation of the SS‐OCTA device used in this study did not allow to segment the MCP separately.…”
Section: Discussionmentioning
confidence: 99%
“…; Onishi et al. ), which is currently not available for the 12 × 12 mm area mainly due to the challenge of a lower resolution. However, quantification of a larger area is possible.…”
Section: Discussionmentioning
confidence: 99%
“…This is important because histopathology indicates that this is an early site of damage in diabetic retinopathy . Indeed, several studies have concurred on this . However, the degree to which these vascular changes are related to visual acuity levels or to the risk of visual loss remains unknown.…”
Section: Applications In Retinal Diseasementioning
confidence: 97%